Strategi Penerapan Fiqih Dalam Lembaga Keuangan Dan Perbankan Di Indonesia - Ardi Putra Burhanuddin Noer; Ina Nugraheni; Hosnul Khotimatul Azizah; Ahmad Mu’is (CV. ITTC INDONESIA, 2025)
This study examines how Islamic jurisprudence (fiqh) principles are applied in Islamic finance and banking practices in Indonesia as an effort to achieve justice and economic well-being. Using qualitative and normative methods through literature review and regulatory comparison, this study finds that Islamic jurisprudence values ​​such as monotheism, justice, prophecy, khilafah, and ma'ad serve as the operational foundations of Islamic banking institutions. The implementation of these principles is evident in the use of various Islamic contracts, the role of the Sharia Supervisory Board, and the implementation of the prohibition on usury. Fatwas from the National Sharia Council (DSN-MUI), along with government policies, serve to ensure compliance with Islamic law. Challenges include the existence of two banking systems, the need for regulatory adjustments, and increased public understanding. Overall, the application of Islamic jurisprudence (fiqh) makes a significant contribution to creating a fairer financial system that is oriented towards the interests of the community.